A simply method for the addition of rotenone in Arabidopsis thaliana leaves - Maliandi, María Victoria (2015)
A simple and reproducible method for the treatment of Arabidopsis thalianaleaves with rotenone is presented. Rosette leaves were incubated with rotenone andTriton X-100 for at least 15 h. Treated leaves showed increased expression of COX19 and BCS1a, two genes known to be induced in Arabidopsis cell cultures afterrotenone treatment. Moreover, rotenone/Triton X-100 incubated leaves presented aninhibition of oxygen uptake. The simplicity of the procedure shows this methodology useful for studying the effect of the addition of rotenone to a photosynthetic tissue in situ.